Нормативне регулювання, сучасний стан поводження та перспективи енергетичного використання твердих побутових відходів в Україні - Haponych L.S.; Golenko I.L.; Topal А.І. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
Existing legislation related to the management of waste in the European Union (EU) and Ukraine has been considered. The obligations taken by Ukraine in the field of waste management according to the Agreement on Association between the EU and Ukraine have been highlighted.These obligations require crucial change in waste management, including municipal solid wastes (MSW). About 5% of MSW is being treated currently in Ukraine, including high-temperature utilization that covers only 2%. The rest not-treated MSW is disposed to the landfield and bulk dumps. However, according to the National Strategy of Waste Management in Ukraine by the year of 2030, the degree of MSW treatment should be increased to 50%, including the extent of MSW thermal utilization to 10% (3 mln tons of MSW). It is planned to achieve such a level of treatment ly the building of new 19 MSW heat treatment factories.Information regarding the amount of MSW produced and treated in Europe and Ukraine is generalized. Current situation related to the management of MSW worldwide and in Ukraine was analyzed. It was shown that the main trend in MSW management in EU’s countries lies in their complex (integrated) treatment such as separate gathering, sorting, mechanical and biological treatment, composting/anaerobic digestion of some parts of MSW, capable for decomposing, and RDF/SRF production from MSW.Different technologies of thermal treatment of waste and RDF/SRF, including incineration, have been briefly considered. The data related to thermal utilization of MSW, amount and productivity of incineration plants in Europe and Ukraine are presented. We generalized information related to the experience of production and use of RDF and SRF in Europe. It was shown that the production and use of RDF/SRF in energy sector have a potential to substitute partly the deficient fossil fuels in Ukraine that are used for electricity and heat production in accordance with ecological EU requirements.The factors affecting the selection of technologies of for MSW thermal treatment for the construction of new incinerating plants in Ukraine are considered, including the requirements of European approaches to waste management.